Thermally induced phase transition and dielectric relaxation in lead-free BaTi0.94Sn0.06O3 Ceramics: Insights from in-situ XRD and XAS - Sukkha, Usa; Chanlek, Narong; Kidkhunthod, Pinit; Kolodiazhnyi, Taras; Vittayakorn, Wanwilai; Vittayakorn, Naratip (My University, 2025)
Lead-free BaTi0.94Sn0.06O3 (BTS) ceramics were synthesized using the conventional solid-state reaction method to investigate thermally induced phase transitions and dielectric relaxation phenomena. A combination of in-situ X-ray Diffraction (XRD) and in-situ Synchrotron X-ray Absorption Spectroscopy (XAS) was employed to examine phase transitions across the temperature range of 200–400 K. The results reveal sequential phase transitions: rhombohedral-orthorhombic (R + O) at 200 K, orthorhombic (O) at 250–300 K, tetragonal (T) at 325–359 K, and tetragonal-cubic (T + C) at 373–400 K. Dielectric measurements highlight an anomalous relaxation behavior at 70–160 K, attributed to domain wall freezing. This phenomenon follows Vogel-Fulcher behavior, with an activation energy of 14 meV, a freezing temperature of 82 K, and an attempt frequency of 4.7 × 106 Hz. X-ray Photoelectron Spectroscopy (XPS) analysis reveals oxygen deficiency on the surface of the BTS ceramic, resulting in the coexistence of Ti3+/Ti4+ and Sn2+/Sn4+ oxidation states. These defects significantly influence the dielectric and phase transition properties. This study provides comprehensive insights into the interplay between local structural changes and phase transition mechanisms in BTS ceramics. By employing a multi-technique approach, it advances the understanding of dielectric and ferroelectric behaviors, positioning BTS ceramics as promising candidates for lead-free dielectric and ferroelectric device applications.
Keywords: BaTiO3; Dielectric; Ferroelectric; Local structure; Phase transition